Adaptive Management for Resilient Internet of Health Things Communication - Nakayama, Fernando; Nogueira, Michele (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2024)
Nowadays, one of the primary goals of the healthcare sector is integrating multiple technologies to monitor and keep track of the distinct clinical parameters of patients. In this regard, the Internet of Health Things (IoHT) is one of the most relevant concepts. IoHT offers communication between healthcare devices and the Internet, the continuous sensing of personal and environmental data, remote care, and insights into symptoms and treatments. However, the heterogeneous nature of devices and technologies, data sensitivity, and privacy-related issues make security a priority in IoHT. Also, IoHT applications transmit critical data, demanding stringent requirements for communication performance. This thesis addresses the crucial security and performance issues in IoHT communication. The hypothesis investigated concerns adding adaptive management throughout IoHT communication levels to increase resilience and preserve the network performance required for healthcare applications. The results from experiments show that adaptive management increases communication resilience and performance when integrated into IoHT.